Union Rates of Talar Neck Fractures with Critical Bone Defects Treated with Autograft. Issue 1 (January 2022) - Patch, David A.; McMurtrie, James T.; Frazier, Mason; Wills, Bradley; Prather, John C.; Viner, Gean C.; Hill, Margie J.; Johnson, Michael D.
Category: Trauma Introduction/Purpose: The purpose of this study was to evaluate union of talar neck fractures with critical bone defects treated acutely with autologous tibial bone graft during primary osteosynthesis. We hypothesized that acute autografting leads to reliable union rates. Methods: A case series at a Level I trauma center was performed to identify patients who underwent open reduction and internal fixation of talar neck fracture with proximal tibial autograft between 2015 and 2018. Inclusion criteria were age greater than 18 years and displaced talar neck fracture with critical bone defect treated with tibial autograft. Critical bone defect was defined as a gap greater than 5mm in the sagittal plane and greater than 1/3 of the width of the talar neck in the coronal plane. Post-operative foot CT scans were obtained for all patients to assess for union. Primary outcome was union and secondary outcomes were malunion, avascular necrosis, post-traumatic arthritis, and patient-reported outcomes (PRO) including PROMIS (Patient Reported Outcomes Measurement Information System), Foot and Ankle Measurements: Activity of Daily Living and Sports (FAAM ADL/Sports), Visual Analogue Scale for feet (VAS), Foot Function Index (FFI), and Short Form-36 (SF-36). Results: Twelve patients were included in the series. The average age was 34 years (17-59). The Hawkins classification of the fractures were four type II (33%) and eight type III (67%). Five fractures (42%) were extruded tali. Four fractures (33%) were open fractures, all being type III fractures. Union was achieved in eleven patients (92%). Nonunion occurred in one patient (8%), who had an open, extruded talus fracture and was a heavy smoker. Avascular necrosis occurred in 11 patients (92%). Ten patients (83%) had radiographic tibiotalar post-traumatic arthritis (PTA), and 12 patients (100%) developed subtalar PTA. Average PROMIS score was 37 (32-45) and average FAAM ADL and Sports was 61 (31-87) and 31 (0-71), respectively. Average VAS was 5 (0-10) and average FFI was 49 (7-89). SF-36 scores showed fair to poor outcomes in the majority of patients. Conclusion: Tibial autograft in primary osteosynthesis of comminuted talar neck fractures with critical bone defects leads to reliable union rates and is an operative strategy that should be considered when treating these difficult fractures. Despite high union rates, secondary outcomes of AVN, PTA, and below-average PRO still occurred in the majority of patients.